2016
DOI: 10.3390/molecules21020083
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Traditional Chinese Medicine Compounds in Xiaoyan Lidan Tablets: Fingerprint and Quantitative Analysis Using UPLC-MS

Abstract: XiaoyanLidan tablets (XYLDTs) are traditional Chinese medicines frequently used for syndromes of the liver and gallbladder, cholecystitis and cholangitis. To evaluate the consistency of the quality of commercial XYLDT preparations, we established a simple and reliable ultra-performance liquid chromatography (UPLC) method with a photodiode array (PDA) detector and mass spectrometry (MS), including a fingerprint analysis and quantification of the main pharmacologically-active markers. In the UPLC-PDA detection-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Ultra-performance liquid chromatography (UPLC) is an improvement of the LC technique. UPLC employs chromatographic principles to separate compounds by utilising columns packed with smaller particles 1.7 μm in size and/or columns with higher flow rates [17]. is technique leads to a shorter analysis time, higher peak efficiency, and higher resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-performance liquid chromatography (UPLC) is an improvement of the LC technique. UPLC employs chromatographic principles to separate compounds by utilising columns packed with smaller particles 1.7 μm in size and/or columns with higher flow rates [17]. is technique leads to a shorter analysis time, higher peak efficiency, and higher resolution.…”
Section: Introductionmentioning
confidence: 99%
“…PCA was also performed on the PPA to ensure that all elements equally influenced the results . Through the eigenvalues and percentage variance determined for each PC (Table ), we found that the first five PCs explained 94.2% of the relevant information.…”
Section: Resultsmentioning
confidence: 99%
“…Modern clinical research indicated that P. quassioides has a significant effect on hypertension (32), pneumonia (67,88), dysentery (89) and other disease symptoms (90,91). Previous studies have also developed various preparations and drugs using P. quassioides, such as Kumu injection, Xiaoyan Lidan tablet (92), Fufang Kumu Xiaoyan capsule (93) and Fufang Kumu Xiaoyan tablet (94). Thus, use of P. quassioides in clinical settings has been gaining considerable attention.…”
Section: Clinical Applications and Developmental Prospects Of Picrasma Quassioides (D Don) Bennmentioning
confidence: 99%